Libraries Stuck in the Middle: Reactive vs. Proactive Responses to the Science Journal Crisis - Elaine Nowick; Claudine Arnold Jenda (Issues in Science and Technology Librarianship)
Libraries and the scholarly community share a dream of creating a world where scholarly articles are easily available on the Internet to everyone who wants them, without any fees, restrictions or barriers of any kind. What is preventing us from fulfilling such a noble and worthy goal? This paper examines selected case studies that show how libraries and scholars are coping with the science journal crisis. By highlighting responses that are innovative and proactive, this paper hopes to contribute to a general awareness of responses that have the potential for transforming the current scholarly communication process into an open, unimpeded, author-controlled electronic-journal based scholarly communication process.